A Comparison of The Programmes Using Finite Element Software in Electrical Machine Design - Murat TOREN; Mehmet ÇELEBI (International Journal of Applied Methods in Electronics and Computers, 2016)
Electrical machines technology has become too dependent on finite element method (FEM) programs in our time. In this study, three programs that are sold commercially are compared over a 4-poles asynchronous machine of 1.1 kW. With this comparison, it is investigated how close the values obtained by convenience, appearance, integration and, in particular, torque calculations with the real values will be. For this, the mechanical torque value of the machine is obtained first by using the machine’s foreknown geometrical parameters and electrical parameters found by tests. Then, the magnetic flux line and density distribution and the obtained reluctance / real torque values are compared between FEM programs.